Dance, Bravo! Magazine, the Education of the Public: cultural reverberations of pedagogical ideas - Mônica Evelyn dos Santos; Julio Groppa Aquino (Revista Brasileira de Estudos da Presença, 2021)
In order to analyze the relationships between dance and education from a perspective not limited to teaching the artistic practice, this study examined articles on dance published in the cultural magazine Bravo! (1997 to 2013). From the categorization of three major themes - classical ballet and its disciplinary content; ethnic and popular aspects of Brazilian contemporary dance; and the building of an audience for dance - an analysis of the material verified the emergence of a pedagogical bias in the magazine’s discourse, expressed in a proliferation of imperatives aimed at educating the dance audience.